Strategi pemasaran pada the ritz carlton spa nusa dua bali - Swandewi, Ni Wayan Anik; Sulistyawati, Agung Sri; Arismayanti, Ni Ketut (Jurnal Kepariwisataan dan Hospitalitas; Vol 5 No 1 (2021): Vol.5,No.1,2021, 2021)
This research is motivated by tourist visits that do not meet the target of several years such as 2015 and 2017 and the percentage of tourist visits staying at hotels is also very minimal despite several sales promotions. The high average hotel occupancy does not make all tourists staying at The Ritz Carlton Hotel visit the spa. In 2015, only 29.7% of tourists stayed at The Ritz Carlton hotel out of the total hotel occupancy that visited the spa. In 2016 recorded 6.6%, in 2017 recorded 5.9% and in 2018 recorded 6.7% of the total occupancy who visited the spa. Along  with the lack of tourist visits from outside the hotel to the spa. Considering that other five-star hotels in the Sawangan area, The Ritz Carlton hotel is still relatively new. This study aims to determine the internal and external environment and marketing strategies of The Ritz Carlton’s Spa.           The data analysis technique used in this study was qualitative descriptive analysis and SWOT analysis was assisted by a Likert scale technique. Data collection techniques are obtained from the results of observations, interviews, questionnaires, literature studies and documentation. The informant determination technique used is Purposive Sampling. The sampling technique uses the Slovin formula totaling 100 respondents with accidental sampling as the distribution of the questionnaire. The results of the study stated that the internal environment contained 9P segmenting, targeting and positioning as well as the marketing mix. The external environment contains political, legal, economic, socio-cultural, technological and media environment factors. The SO strategy is a strategy for creating new treatment programs or healing programs based on Balinese cultural traditions. WO strategy is a strategy to improve the quality of human resources in order to provide maximum service. The ST strategy further introduces the Ritz Carlton Spa brand. WT's strategy is to improve the quality of products and services in order to compete in the market.   Keywords: Strategies, Marketing, Spa, Hotel